Avaliação da atividade antiviral dos peptídeos ZMAVP1 e ZM-AVP2 contra o herpesvírus humano 1 (HHV-1) - Santana, Mateus Costa de (2019)
Viral infections represent a significant concern for the public health and socioeconomic systems, being responsible for infectious diseases with high morbidity and mortality worldwide. Drugs used in the viral infections’ treatment usually act directly on the viruses’ multiplication cycle, and to prevent the formation of new viral particles. Nonetheless, the antiviral drugs’ limitations in the treatment, as viral resistance and their side effects, propel the research and development of molecules with biotechnological potential for new therapeutic approaches. Therefore, antiviral peptides constitute molecules with potential against viral infections of medical importance, such as human herpesvirus 1 (HHV-1), which causes cold sores with a prevalence of 60-95% worldwide. The objective of this project constituted to define the antiviral activity of different peptides as a possible biotechnological product against infections caused by HHV-1. The viral titer reduction method was used to determine the antiviral effect of the peptides against HHV-1, which were cultured in mammalian cells (Vero cell). Initially, an antiviral screening was performed using the synthetic rondonin, PaDBS1R6, ZM-AVP1 and ZM-AVP2 peptides against HHV-1 in their maximum non-toxic concentrations (MNCT). As a result of this evaluation, the ZM-AVP1 and ZM-AVP2 peptides were selected, in which they were able to inhibit the infection in 94.5% and 96.7% using 200 μg.mL-1 per suspension, respectively. The remaining peptides showed no inhibitory effects against HHV-1. The effective concentration of 50% inhibition (EC50) of the peptides was defined by the dose-response curve in 9.2 μg.mL-1 for ZM-AVP1, and at the 34.9 μg.mL-1 for ZM-AVP2. Our results suggest ZM-AVP1 as an entry inhibitor of HHV-1 (85.4%), by possible interaction site with cellular receptors, and ZM-AVP2 as an intracellular inhibitor (46.8%). The peptides selectivity index was >40 for ZM-AVP1, and >11 for ZM-AVP2 when considering the CC50 of both molecules as >400 μg.mL-1. Those results, however, need to be expanded with other tests, broadening viral strains tests to confirm the antiviral potential of the peptides ZM-AVP1 and ZM-AVP2 against HHV-1 and other viral infections of medical importance. In a first moment, nonetheless, the peptides present a biotechnological potential for the treatment of viral infections caused by HHV-1 and are promising candidates for future therapeutically protocols.